IMPLEMENTASI SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN OLEH SEORANG IBU YANG MASIH MEMILIKI ANAK BERUSIA DINI - M. Ridho Ramadani; Nurmita Noviyanti Cane; Rendhy Arief Rahman (INTELIGENSIA MEDIA, 2025)
persecution as stated in the Criminal Code, regulated in Article 351 of the Criminal Code, namely Persecution is punishable by a maximum imprisonment of 2 years and 8 months or a maximum fine of four thousand five hundred rupiah. Humans have different personalities from one another, both in character, differences in goals and outlooks on life, and others. These differences can sometimes trigger the interaction process and can trigger conflicts either based on different interests (conflict of interest) which then causes reactions either subtly in the form of conflict of ideas or harshly in the form of violence. Efforts to implement and enforce the law really need an effective mechanism in order to guarantee the welfare of all citizens. In addition, a legal product is also needed that can regulate in order to support all regulations that regulate all actions in people's lives